2008
DOI: 10.1111/j.1365-3040.2008.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐induced degradation of storage starch in turions of Spirodela polyrhiza depends on nitrate

Abstract: Light induces both the germination of turions of the duckweed Spirodela polyrhiza and the degradation of the reserve starch stored in the turions. The germination photoresponse requires nitrate, and we show here that nitrate is also needed for the light-induced degradation of the turion starch. Ammonium cannot substitute for nitrate in this regard, and nitrate thus acts specifically as signal to promote starch degradation in the turions. Irradiation with continuous red light leads to starch degradation via aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The high TN and TP concentrations in floating turions would support their sprouting and growth, because more TN and TP (especially more TP) are allocated to RNA for synthesis proteins that required for growth . For example, previous studies determined that the turion germination process (starch breakdown and growth of new photosynthetic organ) of Spirodela polyrhiza depends on the availability of nitrogen source to achieve the necessary energy metabolism and biosynthesis reactions .…”
Section: Discussionmentioning
confidence: 99%
“…The high TN and TP concentrations in floating turions would support their sprouting and growth, because more TN and TP (especially more TP) are allocated to RNA for synthesis proteins that required for growth . For example, previous studies determined that the turion germination process (starch breakdown and growth of new photosynthetic organ) of Spirodela polyrhiza depends on the availability of nitrogen source to achieve the necessary energy metabolism and biosynthesis reactions .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have taken advantage of ABA as an inducer and could reproduce the morphological changes that occur during turion formation. Turions are germinated into new fronds in the presence of light and nitrogen in the following spring using starch storage as an energy source [26,27]. Therefore, the drastic starch accumulation during turion formation marks a turning point in the switch process from low-starch fronds to high-starch turions.…”
Section: Discussionmentioning
confidence: 99%
“…As turions cannot take up nutrients from the surrounding environment until new roots/shoots are formed, the main function of turions’ storage could thus be supporting the growth of new roots/shoots . Moreover, recent studies reported that red light pulses induce starch degradation in turions , suggesting the sprouting and establishment of P. crispus turion could be also controlled by light condition. Although, previous studies indicated that high summer temperature and high light conditions might inhibit the sprouting and seedling growth of P. crispus turions , the effects of stress on floating and sinking turions are not yet clear.…”
Section: Introductionmentioning
confidence: 99%